Translation and ophthalmology during the Abbasid Era: Hunayn bin Isḥāq’s ‘In the Eye, Two Hundred and Seven Issues’ as a model of medical scholarship - Dalal H. Al-Zubi; Maamoun Abdulkarim; Mesut Idriz; Shehdeh Fareh; Saleh Al-Leheabi (Cogent Arts & Humanities)
This study explores the contributions of Hunayn bin Isḥāq al-Abbadi (d. 873 AD) to the fields of translation and ophthalmology in the Abbasid era. Focusing on the first fifty questions from his own innovative work In the Eye, Two Hundred and Seven Issues, it examines Hunayn’s innovative approach to Arabizing medical terminology, which avoided literal translations and expanded Arabic vocabulary, particularly in ophthalmology. His medical insights include identifying the eye’s anatomical layers and the one responsible for vision. Through detailed textual analysis and a review of prior studies, the research highlights how Hunayn influenced the Islamic translation movement, his translation methodology, and his medical achievements. The findings highlight his pivotal role in enriching Arabic medical terminology and advancing ophthalmology. His work reflects the methodological rigor of Abbasid scholars, blending linguistic precision with scientific expertise. These efforts not only elevated the translation movement but also refined both language and medical knowledge during the era.